(untitled) (Bangladesh Journal of Botany, 2024)
Semi-natural lakes are important due to their natural diversity and various ecosystem services. Assessment of phytodiversity and water quality can add value in a limnological point of view. The present study was conductedon a semi-natural Madhabpur Lake inBangladesh to estimate diversity and water quality. Samplings were carried outin May 2016 and April 2017. In the lake, phytoplankton belonged to 6 distinct divisions. Chrysophyta and Chlorophyta were thedominantgroups in terms of density.A total of 70 phytoplankton taxa were recorded, of which Cryptomonaserosa var. reflexa, Cyclotellacomta, Ankistrodesmus spiralis, Monoraphidiumarcuatum, Cyclotellacomensis were dominant followed by Ankistrodesmus falcatus, Trachelomonas compacta, Trachelomonas volvocina, Lepocinclis sp. and Mallomonas sp. The mean Chl a recordedin this lake was6.08 µg/l and 8.48 µg/l in 2016 and 2017, respectively. Among the macrophytes, Potamogeton crispus, Monochoria hastata, Myriophyllum heterophyllum, Myriophyllum indicum, Nymphaea stellata, and Nymphoides cristatum were the dominant species in the lake. The calculated water quality index (WQI) showedall sampling stations were “Excellent” in water quality status except for two stations in 2016. WQI also showed that the values were less in 2017 than in 2016, whichmay be due to the addition of more parameters in the calculation. The limit ofphysicochemical parameters for drinking water wascompared with the WHO and ECR guidelines and showed no concern for drinking. So, the lake wateris considered as permissible for human consumption. Bangladesh J. Bot. 53(1): 141-152, 2024 (March)